2018
DOI: 10.1038/s41431-018-0206-3
|View full text |Cite
|
Sign up to set email alerts
|

De novo ITPR1 variants are a recurrent cause of early-onset ataxia, acting via loss of channel function

Abstract: We explored the clinico-genetic basis of spinocerebellar ataxia 29 (SCA29) by determining the frequency, phenotype, and functional impact of ITPR1 missense variants associated with early-onset ataxia (EOA). Three hundred thirty one patients from a European EOA target cohort (n = 120), US-American EOA validation cohort (n = 72), and early-onset epileptic encephalopathy (EOEE) control cohort (n = 139) were screened for de novo ITPR1 variants. The target cohort was also screened for inherited ITPR1 variants. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 23 publications
(26 reference statements)
3
49
0
Order By: Relevance
“…if compared with previously reported SCAR14 patients with homozygous loss of function mutations [3][4][5]. Similar frequencies have been observed for mutations in other SCA-associated loci such as ITPR1[24][25][26] or CACNA1A,27 whereas both autosomal recessive and dominant modes of inheritance associated with neurodevelopmental and/or neurodegenerative features have been reported in KCNC3 28 or GRM1 29,30 mutated families. The challenge will be to decipher subtle changes underpinning Purkinje cells dysfunction both in early and later stages of these various forms of ataxia.…”
supporting
confidence: 81%
“…if compared with previously reported SCAR14 patients with homozygous loss of function mutations [3][4][5]. Similar frequencies have been observed for mutations in other SCA-associated loci such as ITPR1[24][25][26] or CACNA1A,27 whereas both autosomal recessive and dominant modes of inheritance associated with neurodevelopmental and/or neurodegenerative features have been reported in KCNC3 28 or GRM1 29,30 mutated families. The challenge will be to decipher subtle changes underpinning Purkinje cells dysfunction both in early and later stages of these various forms of ataxia.…”
supporting
confidence: 81%
“…In this study, we have examined the consequences of a representative set of missense mutations on IP3R channel function that are illustrative of mutations in distinct functional domains of the IP3R and of differing modes of inheritance. Missense mutations of residues Arg269 (R269W) (50)(51)(52)(53) and Asn602 (N602D) (47,48,52) both lead to multiple cases of autosomal dominant, early onset, nonprogressive ataxia, even though they are located in the LBD and regulatory/coupling domain, respectively ( Figure 1A and Figure 1B). In contrast the G2498S mutation, located in the c-terminal selectivity filter of the IP3R2 channel pore ( Figure 1C) is inherited in an autosomal recessive fashion such that individuals homozygous for the mutation suffered from generalized anhidrosis while their family members heterozygous for the mutation were asymptomatic for the disease (55).…”
Section: Introductionmentioning
confidence: 99%
“…However, a small ZHp in the ITPR1 region from the current study indicated species specificity in plateau adaptive molecular mechanisms. Furthermore, recent reported heterozygous mutations and structural variants of ITPR1 genes are associated with the development of ataxia in the brains of human children (De Silva et al, ; Synofzik et al, ). As we know, plateau hypoxic environmental stimulation leads to an increase in the ratio of [HCO3‐]/[H2CO3] in the cerebrospinal fluid of animals, leading to the inhibition of central chemoreceptors, thus resulting in brain ataxia (Hainsworth, Drinkhil, & Rivera‐Chira, ).…”
Section: Resultsmentioning
confidence: 99%